LINGUISTIC AND EXTRALINGUISTIC ANALYSIS OF SOMATIC COMPONENT PHRASEOLOGICAL UNITS IN ENGLISH AND UZBEK LANGUAGES - Qulatova Mohira Mamatqulovna (Web of Journals Publishing, 2025)
This paper explores the linguistic and extralinguistic aspects of somatic component phraseological units (SCPU) in English and Uzbek. Building upon the works of scholars such as Zoltán Kövecses (2002) and Uzbek linguist M. Shodmonov (2006), this study reveals structural, functional, and cultural dimensions of SCPUs. The analysis follows the IMRAD format and uses both qualitative data and theoretical frameworks to emphasize how somatic elements (e.g., body parts) in idioms reflect cultural cognition and socio-linguistic identity.This paper explores the linguistic and extralinguistic aspects of somatic component phraseological units (SCPU) in English and Uzbek. By drawing on examples from both languages, this study reveals similarities and differences in structure, usage, and cultural significance. The analysis is guided by the IMRAD format, focusing on methodology, comparative data, and interpretive insight. The paper emphasizes how somatic elements (e.g., body parts) are embedded in idiomatic expressions, serving as a window into cultural and conceptual cogntion.
Keywords: Phraseology, somatic components, idioms, English, Uzbek, linguistic analysis, extralinguistics, culture.